2020
DOI: 10.3390/ijerph17207398
|View full text |Cite
|
Sign up to set email alerts
|

Motives and Commitment to Sport in Amateurs during Confinement: A Segmentation Study

Abstract: The current COVID-19 pandemic has paralysed whole countries, which have had to confine their entire population and this changed people’s lives worldwide. The aim of this study is to identify the reasons for and the level of commitment to physical activity among the Spanish population during confinement and the return to the “new normal”. A sample of 1025 amateurs, 534 males and 491 females with an average age of 35 years old were interviewed using an online survey that collected their motives for practising sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 71 publications
1
17
0
4
Order By: Relevance
“…Despite our fairly small sample compared to other recent publications on the topic, this effect is large and needs further investigation. In future, not only should motivation be assessed more objectively but motivation to exercise should also be assessed, as this is related to exercise commitment, also during a lockdown ( Angosto et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite our fairly small sample compared to other recent publications on the topic, this effect is large and needs further investigation. In future, not only should motivation be assessed more objectively but motivation to exercise should also be assessed, as this is related to exercise commitment, also during a lockdown ( Angosto et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…In detail, it has shown that motivational aspects, which belong to the psychological modalities (i.e., motivation, emotion, cognition, volition) of the biopsychosocial states, have decreased in athletes (see di Fronso et al, 2020 ). In amateur athletes, rate of commitment to sport has remained high at 61.6% (30.7% moderate; 7.7% low commitment; see Angosto et al, 2020 ). Another study showed that for the period before to during the confinement, goals shifted and predict the intention to exercise during confinement ( Mascret, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Different studies indicated that, in the endurance modalities, high levels of addiction were registered and the participants continued with the practice in spite of being injured [ 50 ], and, moreover, they persisted in spite of the negative consequences caused by not running in the best physical condition, because the reward they obtained was greater than any reward for not doing so [ 51 ]. Recent studies indicate that the COVID-19 pandemic has apparently influenced an increase in the active population to be more physically active than before the pandemic, in Spain and the United Kingdom [ 34 , 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…They have largely highlighted entirely predictable drops in PA between pre- and during lockdown, with short durations of follow-up. These drops likely reflect the temporary restrictions, uncertainty, caution and changes in motivation and commitment [ 21 ]. What is not known, and is perhaps of more long-term relevance, is how PA went on to change from the point of lockdown onwards, including subsequent periods when rules were relaxed but some social restrictions remained in place.…”
Section: Introductionmentioning
confidence: 99%